Road Network Connectivity Quality Assesment for Timor Leste National Road Network - Frans de Jesus Babo; Hitapriya Suprayitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Timor Leste is a very young country. Road network is still pretty the only blood vessel of the economy. Road network need to be well managed following the principle of Infrastructure Asset Management. Thus, the national road network still has to be evaluated against the primary network quality: the connectivity. Assessment indicated that all national center activities are connected by national road network. But, the connectivity cannot be said to be good enough for certains. Due to the mountainous and hilly area, the roads still need to be improved in term of road cross section and road geometry.